Long-Term Hydraulic Adjustment of Three Tropical Moist Forest Tree Species to Changing Climate - Islam, Mahmuda; Rahman, Mizanur; Bräuning, Achim (Frontiers in Plant Science, 2018)
Xylem hydraulic adjustment to global climate changes was reported from temperate, boreal and Mediterranean tree species. Yet, the long-term hydraulic adjustment in tropical trees have not been studied so far. Here we developed the first standard chronologies of three hydraulic trait variables for three South Asian moist forest trees to analyze their long term hydraulic responses to changing climate. Based on wood anatomical measurements, we calculated Hagen–Poiseuille hydraulically weighted vessel diameter (DH), potential specific hydraulic conductivity (KS), and vulnerability index (VX ) and developed standard chronologies of these variables for Chukrasia tabularis, Toona ciliata, and Lagerstroemia speciosa which are different in their shade tolerance, xylem structure, wood density, growth rates and habitat preferences. Bootstrap correlation analysis revealed that vapor pressure deficit strongly positively influenced the xylem water transport capacity in C. tabularis, whereas T. ciliata was affected by both temperature and precipitation. The hydraulic conductivity of L. speciosa was mainly affected by temperature. Differential adjustment strategies were observed among the species, probably due to the differences in life history strategies and xylem properties. No positive relationship of conductivity and radial growth was found, but a trade-off between hydraulic safety and efficiency was observed in all studied species.